Effects of a point source of phosphorus on the arsenic mobility and transport in a small fluvial system. (15th December 2022) - Venhauerova, Petra; Drahota, Petr; Strnad, Ladislav; Matoušková, Šárka
Abstract: One of the leading causes of As release from streambed sediments into freshwater systems is competition with phosphate. Among important sources of P to the fluvial ecosystems are wastewater treatment plants (WWTP), estimated to account for 25–45% of all P in surface waters. In this paper, long-term effects of discharged phosphorus from a small WWTP on the arsenic mobility were studied in an As-enriched fluvial system (approx. 240 mg/kg) in central Czech Republic. After 7 years of elevated P (≤7.7 mg/L) in the stream water, the total As decreased by 25% and the total P increased by 40% in the sediments downstream (at a distance of 66 m). The results of the chemical extractions and mineralogical analyses indicated that the changes in the concentration were mostly due to the sorption processes in the Fe (oxyhydr)oxides (goethite and hematite). In the downstream samples, the As in these phases decreased two-fold, and P was significantly enriched by 45–140%. Phosphorus was also found precipitated as newly formed Ca phosphates. The stream water monitoring indicated that the discharged P was either sequestered when the levels of dissolved P were high (>2.3 mg/L) or released from the downstream sediments when these levels were low (<∼1.5 mg/L). Meanwhile, As was continuously mobilized from the downstream sediments likely due to (i) the ongoing As desorption from the exterior parts of the Fe (oxyhydr)oxides at high aqueous P levels and (ii) the dissolution of As-bearing Ca phosphates at low dissolved P levels. These findings clearly demonstrate that point sources of P to streams and rivers, such as WWTP, may result in the permanent and long-term release of As from contaminated streambed sediments. Graphical abstract: Image 1 Highlights: Effluent may permanently and over long-time release As from sediments. Elevated P (≤7.7 mg/L) in the stream water causes a decrease in bound As. Discharged phosphate adsorbs and precipitates as Ca phosphates. Phosphate competes with As for sorption sites on Fe (oxyhydr)oxides.